Glycine Attenuates LPS-Induced Apoptosis and Inflammatory Cell Infiltration in Mouse Liver. Issue 5 (26th February 2020) - Zhang, Yunchang; Jia, Hai; Jin, Yuhang; Liu, Ning; Chen, Jingqing; Yang, Ying; Dai, Zhaolai; Wang, Chao; Wu, Guoyao; Wu, Zhenlong
ABSTRACT: Background: Liver dysfunction impairs immunological homeostasis. Glycine (Gly) has been reported to have antioxidative and anti-inflammatory effects and to regulate apoptosis in various models. Objectives: The aim of the present study was to determine whether Gly could attenuate LPS-induced liver injury. Methods: In Experiment 1, 48 6-week-old male C57BL/6 mice were randomly assigned into one of 4 groups: CON (control), GLY [orally administered Gly, 5 g · kg body weight (BW) −1 · d −1 for 6 d], LPS (5 mg/kg BW, intraperitoneally administered), and GLY + LPS (Gly supplementation, and on day 7 LPS treatment). In Experiment 2, mice were untreated, pretreated with Gly as above, or pretreated with Gly + l -buthionine sulfoximine (BSO) (0.5 g/kg BW, intraperitoneally administered every other day) for 6 d. On day 7, mice were injected with LPS as above. Histological alterations, activities of antioxidative enzymes, apoptosis, and immune cell infiltration were analyzed. Results: In Experiment 1, compared with CON, LPS administration resulted in increased karyolysis and karyopyknosis in the liver by 8- to 10-fold, enhanced serum activities of alanine transaminase (ALT), aspartate transaminase (AST), and lactate dehydrogenase (LDH) by 1- to 1.8-fold, and increased hepatic apoptosis by 5.5-fold. Furthermore, LPS exposure resulted in increased infiltration of macrophages and neutrophils in the liver by 3.2- to 7.5-fold, elevated hepatic concentrations of malondialdehyde and hydrogen peroxide (H2 O2 ), and elevated myeloperoxidase (MPO) activity by 1.5- to 6.3-fold. In Experiment 2, compared with the LPS group, mice in the GLY + LPS group had fewer histological alterations (68.5%–75.9%); lower serum ALT, AST, and LDH activities (24.3%–64.7%); and lower hepatic malondialdehyde and H2 O2 concentrations (46.1%–80.2%), lower MPO activity (39.2%), immune cell infiltration (52.3%–85.3%), and apoptosis (69.6%), which were abrogated by BSO. Compared with the GLY + LPS group, mice in the GLY + BSO + LPS group had lower hepatic activities of catalase, superoxide dismutase, and glutathione peroxidase by 33.5%–48.5%; increased activation of NF-κB by 2.3-fold; and impaired nuclear factor (erythroid-derived 2)-like 2 signaling by 38.9%. Conclusions: Gly is a functional amino acid with an ability to protect the liver against LPS-induced injury in mice.